2012
DOI: 10.2174/138920012799362828
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HIV Inhibitors Guided by Free Energy Perturbation Calculations

Abstract: Free energy perturbation (FEP) theory coupled to molecular dynamics (MD) or Monte Carlo (MC) statistical mechanics offers a theoretically precise method for determining the free energy differences of related biological inhibitors. Traditionally requiring extensive computational resources and expertise, it is only recently that its impact is being felt in drug discovery. A review of computer-aided anti-HIV efforts employing FEP calculations is provided here that describes early and recent successes in the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 191 publications
0
5
0
Order By: Relevance
“…145 Other successful examples include inhibitors of the tautomerase activity of human macrophage migration inhibitory factor (MIF) 146−148 and others. 149 Taken together, these paradigmatic examples attest the impact of FEP calculations on lead optimization for drug discovery, with a clear demonstration that this approach, nowadays, offers great advantages and progress.…”
Section: Coupled To Enhanced Sampling Methods For Investigating Ligan...mentioning
confidence: 99%
“…145 Other successful examples include inhibitors of the tautomerase activity of human macrophage migration inhibitory factor (MIF) 146−148 and others. 149 Taken together, these paradigmatic examples attest the impact of FEP calculations on lead optimization for drug discovery, with a clear demonstration that this approach, nowadays, offers great advantages and progress.…”
Section: Coupled To Enhanced Sampling Methods For Investigating Ligan...mentioning
confidence: 99%
“…Accurate calculation of free energy changes is essential for the characterization of chemical processes. Recent reviews on the FEP calculations and historical perspectives are available . FEP uses the Zwanzig expression (Eq. )…”
Section: Qm/mm/mc Methodology Detailsmentioning
confidence: 99%
“…[6]Development of new classes of FKBP inhibitors may, therefore, serve as treatment for neurodegenerative disorders, such as Alzheimer's and Parkinson's diseases.A detailed understanding of the catalytic mechanism of FKBPs and other PPIases and their molecular interactions will assist and advance the design of new classes of inhibitors. [13,[16][17][18][19][20] One of the earlieststudies of the catalytic mechanism of FKBP by Fischer et al, using computational modeling, showed that a peptide (N-acetyl-Leu-Pro-Phe-methylamide) substrate analogue interacted with FKBP by adopting a type VIaproline turn conformation. [11]A combination of hydrophobic and hydrogen bonding interactions were responsible for the favorable free energy of FKBP-substrate complex formation.…”
Section: Fk506 Binding Protein (Fkbp) 12mentioning
confidence: 99%